Overall crystallization behavior of polypropylene–clay nanocomposites; Effect of clay content and polymer/clay compatibility on the bulk crystallization and spherulitic growth - Pérez, Claudio Javier (2009)
The effect of clay nanoparticles on the overall crystallization (isothermal crystallization, spherulitic growth, and nonisothermal crystallization) behavior of polypropylene (PP) was studied by means of differential scanning calorimetry and polarized light optical microscopy. In addition, the changes produced by the compatibility between the filler and the matrix were analyzed by using more hydrophobic clays or incorporating PP grafted with maleic anhydride (PP-g-MA). Different models were used to predict the relative degree of crystallinity and several parameters were analyzed. A clear nucleating effect of clay nanoparticles was found on the experimental behavior (induction time, half-crystallization time, and overall crystallization time) and also deducted from the models parameters (Avrami exponent, rate constant, nucleation activity, activation energy). The effect was also related with the matrix/clay compatibility. In addition, the polarized light optical microscopy showed that the number of spherulites increased and their size decreased when clay was incorporated, which is also an indication of the heterogeneous nucleating behavior of such particles. We also noted faster spherulitic growth and increasing Kg (the model parameter).